PENINGKATAN USAHA TERNAK KAMBING DI KELOMPOK TANI SUMBER SARI DALAM ANALISIS EKONOMI PENDAPATAN - S. Rusdiana; Rijanto Hutasoit (Universitas Sebelas Maret, 2014)
This research was conducted at the District High King shavings District of North Sumatra Province. The purpose of the study was to determine the increase in goat farming goat farmer groups in the analysis of pollen sources of income. The study was conducted in the village of Sumber High King and High King of Hope in District District shavings, each study site has the same agro-ecosystems. The study was conducted by the method by filling in a questionnaire survey using kuwesioner and structured interviews with 15 respondents farmers and 15 farmer groups koopertor non-cooperators, in November-December 2012, according to the information from the Department of Agricultural Extension and local farming population criteria goats and primary data secondary data collected was analyzed using descriptive tabulation and analysis of the economy.The results of the research effort goat raising net income amounted Rp.8.411.168 Koopertor, 83/tahun, B/C ratio of 1.4, and goat enterprises are non Cooperators sebsar Rp. 1,644,051.24/year, B/C ratio of 1.2. This can increase the income of farmers in maintaining the well-being of families and the need for the application of technological innovations introduced so that a more commercial farming goats and goats can be sustained presence in times to come.